2004
DOI: 10.1097/01.ccm.0000124873.05080.78
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia at admission to the intensive care unit is associated with elevated serum concentrations of interleukin-6 and reduced ex vivo secretion of tumor necrosis factor-α*

Abstract: Our main findings show that admission hyperglycemia is statistically related to distinct changes of humoral and cellular immune functions. Furthermore, elevated glucose concentrations at admission are associated with increased intensive care unit mortality rate in a medical intensive care unit. Although these data do not explain cause and effect, our results provide a strong rationale for studying the immunologic effects of strict glycemic control in the intensive care unit during the course of critical illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 39 publications
(41 reference statements)
1
31
1
3
Order By: Relevance
“…Increases in serum IL-6 and catecholamine concentration have been reported to be associated with insulin resistance and glycogenolysis in the liver [23][24], thus promoting diabetes mellitus. Our patient also showed elevated plasma and urine cortisol levels, which also have been caused by overproduction of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in serum IL-6 and catecholamine concentration have been reported to be associated with insulin resistance and glycogenolysis in the liver [23][24], thus promoting diabetes mellitus. Our patient also showed elevated plasma and urine cortisol levels, which also have been caused by overproduction of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is secreted by macrophages, lymphocytes and other cells [10]. It has been previously reported that hyperglycaemia increases serum concentrations of IL-6 [11,12] possibly through augmented production in monocytes [11,13]. Thus patients with diabetes have elevated blood levels of IL-6, which, together with TNF-α are known to increase inflammation and the development of vascular disease and atherosclerosis, possibly by increasing oxidative stress [12,14,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycemia is a common consequence of critical illness and has a direct correlation with IL-6 levels. 32 Activity can decrease insulin resistance and increase muscle utilization of glucose. 4,32 Possibly, repeated sessions of passive exercise not only decrease blood glucose levels and insulin requirements in critically ill patients but also decrease IL-6 levels.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…32 Activity can decrease insulin resistance and increase muscle utilization of glucose. 4,32 Possibly, repeated sessions of passive exercise not only decrease blood glucose levels and insulin requirements in critically ill patients but also decrease IL-6 levels. The relationship between mobilization, IL-6 levels, blood glucose levels, and insulin requirements in critically ill patients should be explored further.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%